Role of social media on political participation / Muhammad lslah Hadzir and Ahmad Luqman Azim Shukri - Hadzir, Muhammad lslah; Shukri, Ahmad Luqman Azim (2018)
This chapter covers the factors that influence the role of social media on youth political participation. Besides, the researcher also provides the background to the study, the problem statement, research questions which the researcher will produce solution for and research objectives researcher seeks to achieve. Additionally, the researcher also included the scope of study for the level, place and time of where and when the study will take place, the significance of the study along with definition of terms, terminology and concept of the proposed study.